2013
DOI: 10.1103/physrevd.88.074024
|View full text |Cite
|
Sign up to set email alerts
|

MultipleZtt¯signals in a 4D composite Higgs model

Abstract: We study the production of top-antitop pairs at the Large Hadron Collider as a test bed for discovering heavy Z 0 bosons belonging to a composite Higgs model, as in this scenario, such new gauge interaction states are sizeably coupled to the third-generation quarks of the Standard Model. We study their possible appearance in cross sections, as well as (charge and spin) asymmetry distributions. Our calculations are performed in the minimal four-dimensional formulation of such a scenario, namely the four-dimensi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 97 publications
0
14
0
Order By: Relevance
“…This is the reason why a close look at this production process within the 4DCHM was taken in Ref. [12]. Herein, it was shown that the additional Z resonances present in this CHM scenario could greatly affect the phenomenology of tt production at the LHC, through their effects onto both the cross section and (charge and spin) asymmetries, so long that they can be produced resonantly and subsequently decay into top-antitop pairs.…”
Section: Introductionmentioning
confidence: 96%
“…This is the reason why a close look at this production process within the 4DCHM was taken in Ref. [12]. Herein, it was shown that the additional Z resonances present in this CHM scenario could greatly affect the phenomenology of tt production at the LHC, through their effects onto both the cross section and (charge and spin) asymmetries, so long that they can be produced resonantly and subsequently decay into top-antitop pairs.…”
Section: Introductionmentioning
confidence: 96%
“…In short, we believe that our results represent a significant phenomenological advancement in proving that charge and spin asymmetry observables can have a strong impact in accessing and profiling Z → tt signals during Run 2 of the LHC. This is all the more important in view of the fact that several BSM scenarios, chiefly those assigning a composite nature to the recently discovered Higgs boson, embed one or more Z state which are strongly coupled to top (anti)quarks [10].…”
Section: Discussionmentioning
confidence: 99%
“…[15] a two-site quiver is proposed, and its phenomenology of the extended gauge sector is studied in Ref. [16]. A three-site construction more similar to ours is that of Ref.…”
Section: Introductionmentioning
confidence: 94%